Traditional compactness of the urban core: ‘walkability’ and the Malay public realm - Ibrahim, Illyani (Palgrave Macmillan, 2023)
This chapter focuses on identifying the intimacy and compactness in the public spaces of a part of South East Asia’s urban cores. The traditional South East Asia urban cores are the centres of traditional settlements before the disruption due to colonialism. The traditional character has disappeared along with modern urbanisation. This chapter includes three case studies: Alor Setar, Kuala Terengganu, and Kota Bharu. The case studies describe the compactness from the perspective of walkability and liveability of the traditional urban core and the settlement areas. The chapter also suggests that the character of compactness between the royal elements persists over time.